The Role of Social Media Marketing in Enhancing Consumer Purchase Decisions among Local Businesses in Mataram City - Asri Oktiani; Sri Maryanti (Fundamental and Applied Management Journal, 2026)
This research explores the mechanisms through which social media-based marketing activities influence purchasing behaviour among customers of locally operated businesses in Mataram, Indonesia. The study responds to the scarcity of empirical research focusing on digital marketing practices in regional small-enterprise settings. Data were obtained from 250 individuals who had been exposed to and interacted with promotional content published by local businesses on social media. Using a cross-sectional quantitative approach, responses collected through a structured questionnaire were examined through partial least squares structural equation modelling. The analysis first verified the adequacy of the constructs in terms of reliability and validity before evaluating the proposed relationships among the variables. The findings demonstrate that consumer trust is significantly strengthened by content quality, interactivity, informativeness, entertainment, and electronic word-of-mouth. Electronic word-of-mouth produced the largest contribution to trust formation (β = 0.29, p < 0.001). Trust subsequently showed a substantial positive association with purchasing decisions (β = 0.67, p < 0.001). The model accounted for 58% of the variation in consumer trust and 45% of the variation in purchasing decisions. The indirect-effect analysis further established that trust serves as a significant intermediary between each social media marketing dimension and consumer purchasing decisions. These findings extend digital marketing research by offering evidence from a regional Indonesian market and emphasizing that trust-building communication is particularly important for small and locally based enterprises. Practically, local businesses should prioritize credible customer reviews, useful information, responsive interactions, and authentic content to strengthen their digital competitiveness.